SYNTHESIS OF OSMIUM COMPLEXES ON THE BASE OF NEW POLYMERS CONTAINING AMINE AND CARBOXYLIC FUNCTIONAL GROUPS - Yu. M. Sultanov (Вестник Дагестанского государственного технического университета: Технические науки)
Osmium complexes by interaction osmium bipyridyl chloride (Os(bipy)2Cl2) and dimmethylbipyridil chloride (Os(dimebipy)2Cl2) with a number of synthesised polymers on the base of 1-(3-aminepropyl)-imidazole, methylmethacrylate, acrylic acid and butylacrylate have been obtained. It have been shown that osmium complexes of the obtained polymers with bipyridyl chloride and dimmethylbipyridil chloride could be used as effective mediators for reagentless amperometric biosensors.